2021
DOI: 10.1136/bmjopen-2020-045113
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of emergency preparedness measures in response to infectious respiratory disease outbreaks: a systematic review and econometric analysis

Abstract: ObjectivesRespiratory infectious disease outbreaks pose a threat for loss of life, economic instability and social disruption. We conducted a systematic review of published econometric analyses to assess the direct and indirect costs of infectious respiratory disease outbreaks that occurred between 2003 and 2019.SettingRespiratory infectious disease outbreaks or public health preparedness measures or interventions responding to respiratory outbreaks in OECD countries (excluding South Korea and Japan) so as to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…A systematic review on previous respiratory infectious disease outbreaks prior to COVID-19 (56) concluded to similar results by pointing out the significant burden of both direct and indirect medical costs for management and response activities. Most direct costs occured from the additional personnel hours, the response planning and contact tracing activities, the provision of training and educational materials and the laboratory costs.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…A systematic review on previous respiratory infectious disease outbreaks prior to COVID-19 (56) concluded to similar results by pointing out the significant burden of both direct and indirect medical costs for management and response activities. Most direct costs occured from the additional personnel hours, the response planning and contact tracing activities, the provision of training and educational materials and the laboratory costs.…”
Section: Discussionmentioning
confidence: 71%
“…Most direct costs occured from the additional personnel hours, the response planning and contact tracing activities, the provision of training and educational materials and the laboratory costs. Indirect costs were greater than direct ones, particularly when school closures and/or workplace closures were implemented, due to lower productivity (56). However, given the strictness of the NPIs in COVID-19 pandemic the economic burden has been found to be high for primary production sectors including industries associated with activities in raw materials extraction, secondary industrial sectors involving the production of finished products and tertiary sectors encompassing service provision industries (57).…”
Section: Discussionmentioning
confidence: 99%
“…Not only did chronic ischaemic heart disease, hypertension, pneumonia and diabetes display strong statistically remarkable deviations from reference, but these conditions are also prominent morbidities noted in the context of COVID-19 deaths. There is also the possibility that the increase in non-COVID-19 deaths may be partially due to indirect effects related to the pandemic response from several dimensions (eg, incomplete knowledge by healthcare providers of COVID-19 as a novel condition impacting treatment strategies, policy implementation, lockdowns, social and economic dislocations, treatment and lapses in care) 21–28. However, although plausible, our analysis is inadequate to inform on this issue in a dispositive manner.…”
Section: Discussionmentioning
confidence: 97%
“…Specifically, two meta-analyses with a previous cut-off date from our systematic review documented a preventive effect of face masks against COVID-19 in healthcare workers and the general population (24, 25). Also, face masks were found to be important as a preventative strategy, especially when population compliance is high, according to our team’s prior systematic analysis of the cost-effectiveness of public health emergency preparedness strategies (26). These findings are also corroborated by research on previous respiratory infectious diseases.…”
Section: Discussionmentioning
confidence: 99%